Effect of agrotechnological treatment on nutritive value of common millet - Jevcsák, Szintia; Sipos, Péter (Acta Agraria Debreceniensis, 2017)
The cultivation of common millet shows an increasing tendency due to its adaptability to extreme poor circumstances. In addition, millet do not contain gluten forming proteins such as gliadin and glutenin, therefore people with gluten intolerance could consume it. The vitamin B and mineral content increase the importance of millet. The aim of our experiment was to measure the quality of flour of two millet varieties treated with different nitrogen fertilizer doses.